Sie sind auf Seite 1von 29

CHAPTER 2

Discrete-Time Systems and the z-Transform


This chapter covers two main topics, namely Discrete-Time Systems and the z-transformation. We are familiar with the use of differential equations for a continuous-time system. However, a discretetime system is described by set of difference equations. Therefore, before we proceed further, it is necessary for us to learn how to convert from differential equation to difference equation and vice versa. Differential Equation Difference Equation

2.1 Differential representation The term in any differential equation can be replaced by its corresponding difference equation

in two different ways: i) Backward operation = ii) Forward operation = In almost all cases, backward operation is more preferable to use instead of forward operator as backward operator produces only causal system.

Example 2.1 Figure 2.1 shows a simple analog filter of which difference equation needs to be determined. From the law of current,

=
X(T) C Y(t)

or = +

Suppose RC = 1

Figure 2.1 an analog circuit

then.

+ y(t) = x(t)

[analog filter]

Using backward operation, Suppose t = k,

or, (

) y (k) - y(k-1) = x (k) which is the difference equation for the given analog filter.

Similarly, we can represent the differential equations for some of the oft used controllers as below:

P controller differential equation: difference equation : m(t) = Kp e(t) m(k) = Kp e(k)

e(t)

m(t)

Kp

figure 2.2: P controller

PD Controller differential equation: difference equation : m(t) = Kp e(t)+ Kd m(k) = Kp e(k) + Kd =* + e(k) Kd e(k-1)

e(t)

Kp + d/dt figure 2.3: PD controller


m(t)

2.2 INTEGRAL REPRESENTATION An integral in its continuous time is represented as: e(t) = i.e. e [ (k-1) T] =

From the figure 2.2, e(kT) = e[ (k-1) T ] + shaded area The shaded region can be obtained from any of the following three methods: i) Left Hand Rectangular Rule (LHRR) Area = T e[(k-1) T]

ii) Right Hand Rectangular Rule (RHRR) Area = Te (k T)

figure 2.4: Integral representation

iii) Trapezoidal (Tustin) Method Area = [ e (k-1)T + e(kT)

Stability analysis of the three different methods: LHR: For, LHR the difference equation is represented by, m(k) = m(k-1) + Te(k-1) In z-doimain, M(z) = z-1 M(z) + T z-1 E(z) or, In s-domain, = =

Equating to check the stability = or z 1 =Ts or, z = 1 +Ts or z = 1 + T ( + j) Equating the above equation with z = x + jy we get x=1 + T and y = T Next, to represent it in the form of circle, x2 + y2 = r2 x2 + y2 =( 1 + T )2 + (T)2 >1 i.e r > 1, which implies that the value lies outside the unit circle. Hence it is unstable. [. s = + j ]

RHR: For, RHR the difference equation is represented by, m(k) = m(k-1) + Te(k) In z-doimain, M(z) = z-1 M(z) + T E(z) or, In s-domain, = =

Equating to check the stability = or z 1 =Tsz or, zTs z = -1 substituting, s= j

or z =

Equating the above equation with z = x + jy and representing it in a circle form, x2 + y 2 = i.e. x2 + y2 = x or, x2 x + y2 = 0 or, ( ) ( ) + =
2

i.e r = which implies that the value lies inside the unit circle. Hence it is stable but with limitations.

Trapezoidal: For, trapezoidal method the difference equation is represented by, m(k) = m(k-1) + [ e (k-1)T + e(kT) [ E(z) + z-1 E(z) ]

In z-doimain, M(z) = z-1 M(z) + or, In s-domain, = =

Equating to check the stability = or Ts (z + 1) = 2(z -1 ) or, z = substituting, s= j or z = = x = + j

Equating the above equation with z = x + j y and representing it in a circle form, 1 x +y =(


2 2

) +(

) =

i.e. x2 + y2 = 1 or, x2 x + y2 = 0 i.e r = which implies that the value lies inside or on the unit circle. Hence it is stable

The difference equation of some of the controller with integral is given below. e(t) PI Controller differential equation: Using LHRR, difference equation : m(k) = Kp e(k) + Ki [ m(k-1) + T e(K-1) ] figure 2.5: PI controller 2.3 SOLVING A DIFFERENCE EQUATION In general an Nth order difference equation can be written as: m (k) +
n

m(t) = Kp e(t)+ Ki

m(t)

m(k-n) =

e (k-n)

; MN

i.e. first order, N =1 m(k) + a1 m(k-1) = b0 e(k)

Second order, N=2 m(k) + a1 m(k-1) + a2 m(k-2) = b0 e(k) + b1 e(k-1) + b2 e(k - 2) Zero State Response Convolution m(k) = e(k) * h(k)

e(k)

m(k)

Total Response (Complete Response) Two problems to be solved for the determination of controller response m(k) : i) Determination of h(k) This is needed in determining the m(k) via convolution. m(k) = h(k) e(k) = (k) Basic DT signals Kronecker Delta Sequence, Unit pulse Sequence (k) = , 0 (k-n)= , ii) Determination of m(k) This can be obtained by direct solution of the difference equation. 0 0

Example 2.2 Given: m(k) + 0.6 m(k-1) = 2 e(k) Determine h(k) and hence obtain the zero state response of the controller. (zero state response system is completely relaxed. Hence no initial condition) Solution m(k) = h(k) e(k) = (k) h(k) + 0.6 h(k-1) = 2 (k) for k>0 h(k) + 0.6 h(k-1) = 0 substituting h(k) = c k c k + 0.6 c k -1 = 0 c k -1 ( + 0.6) = 0 .. = -0.6 h(k) = C (-0.6) k u(k) For k=0, h(0) + 0.6 h(-1) = 2 (0) for causal system h(-1) = 0 also (0) = 1 [unit pulse sequence] Basic DT signals Unit Step Sequence u (k) = , 0 0 0

Ramp Sequence r(k) = = , 0

Linear time invariant causal system Causal System h(k) = 0 , k<0

.. h(0) = 2 Hence, h(k) = 2 (-0.6) k u(k) h(k) e(K) m(K)

m(k) = T {e (k) } e(k) = m (k) = T { m(k) = m(k) = { } } DT convolution (Reflection, Multiplication, shifting and summation)

Coming back to the remaining part of the solution, i.e finding m(k) m(k) = 0 0
n n

== 2 = 2

u(l) u(k-l)

.. m(k) = 2 ( = 1.25 [

) 0

Recall
n

Try: 1. Repeat the above problem by replacing 0.6 with 0.8 2. Repeat the above problem with the following difference equation m(k) 0.8 m (k-1) = 2 e (k) + e (k-1) 3. What is the difference between solution 1 and 2?

Example 2.3 Solving the controller response problem with initial conditions Given m(k) + m (k -1) + m (k -2) = e (k) + 2 e (k -1)

Determine the complete response to input sequence excitation e(k) = u(k) if m(-1) = m (-2) = 1 solution m(k) = mc (k) + mf (k) where, mc (k) due to zero input response mf (k) due to the system excitation to obtain mc (k):

m(k) +

m (k -1) + m (k -2) = 0

let m (k) = c k , c k + or, c k-2 , or, or, ( )( .. = - =0 )=0 , =-ck -1 + c k - 2 = 0 -=0

mc (k) = c1 ( Next, to obtain mf (k):

) c2

e(k) u(k) A sin k k u (k)

mf (k) K u(k) K1 A sin k + K2 cos k (K1 + K2 K) u(k)

From the table 2.1, for e(k) = u(k), mf (k) = K u(k), where K is a constant Recall, m(k) + m (k -1) + m (k -2) = e (k) + 2 e (k -1)

ak u(k) K ak u (k) Table 2.1

Substituting mf (k) = K u(k) and e(k) = u(k) K u(k) + for k 2 K + K+ K =1+2 K u(k-1) + K u (k -2) = u (k) + 2 u (k -1)

or 2K = 3 .. K =

Hence, Total response is given by: m(k) = mc (k) + mf (k) m(k) = c1 ( ) ( ) c2 +

In order to obtain c1 and c2 Initial conditions: m(-1) = m (-2) = 1 for k = 0; m(0) + m ( -1) + m ( -2) = e (0) + 2 e ( -1) for causal system, e(-1) = 0, e(0) = 1

m (0) + + i.e m(0) = 1 -

+ =1+0 =0

for k = 1, m(1) + m ( 0) + m ( -1) = e (1) + 2 e ( 0) for causal system, e(1) = 0, e(0) = 1 m (1) +0 + i.e. m (1) = 2 then, m(0) = 0 = c1 ( or, 0 = c1 + c2 + i.e. 2 c1 + 2 c2 + 3 = 0 ------------------------------i) Also, m(1) = 2 = c1 ( or, 0 = c1 ( ) ) + c2 ( ( )+ ) c2 + ) ( ) c2 + =1+2

i.e. 2 c1 + 3 c2 - 3 = 0 ------------------------------ii) solving equations i) and ii) c1 = 7.5, c2 = 6 Total response: m(k) = [ ( ) ( ) ] u(k)

Try, Given the difference equation m(k +2) m (k + 1) + where m (0) = m(1) =0, e (0) = 0, and e(k) = 1, k = 1,2.. solve for y(k) as a function k.

2.4

Z TRANSFORMATION

The z transform method is an operational method that is very powerful when working with discretetime systems. The z transform of a time function x(t), where t is nonnegative, or of a sequence of values x(kT), where T takes zero or positive integers and T is the sampling period is defined by the following equation,

X(z) = Z [ x(t) ] = Z [ x(kT)] = or, X(z) = Z [ x(k) ] =

Z transformation of some of the elementary functions: i) Unit- step function e(k) = 1 E(z) = = 1 + z-1 + z-2 + z-3 + = =

ii) e(k) = u(k 1) E(z) = = = z-1 + z-2 + z-3 + = z-1 [1 + z-1 + z-2 + z-3 +] = z-1 * + =

iii) m(k) = ( M(z) = =1+ = (

) u(k) ) ( ) + ( ) +.

Recall
k

iv) m(k) = M(z) = -

) u(-1 - k) ( )

replace k by k =- ( ) ) ( ) + ( ) +.

= 1 -1 - ( = =
( )

v) e(k) = (k) E(z) = = 1. z-0 = 1

vi) e(k-n) u(k) E(z) = let l = k-n k= 0, l = -n k= , l = E(z) = = [ + ] , k=l +n

eg.

e(k-2) then its z transformation is given by E(z) = [ 2 ]

vii) e(k+n) u(k) E(z) = let l = k+n k= 0, l = n k= , l = E(z) = = = [ + ] , k=l -n

eg.

e(k+3) then its z transformation is given by E(z) = [ 0 2 ]

2.5

THE INVERSE z TRANSFORM

The z transformation serves the same role for discrete-time control systems that the Laplace transformation serves for continuous-time control systems. For the z transform to be useful, we must be familiar with methods for finding the inverse z transform. The inverse z transform of X(z) yield the corresponding time sequence x(k).

There are three methods commonly used for obtaining inverse z transform. i) Power series method: In power series method, we obtain the inverse of z transform by expanding X(z) into an infinite power series in z-1.

ii) Partial Fraction expansion: In partial fraction expansion method, to find the inverse z transform of X(z), it is expanded into a sum of simple first-or second-order terms by partial fraction expansion which is subsequently converted to corresponding time function using a z transformation table.

iii) Inversion Formula method (Residue theorem method) Residue theorem is perhaps one of the quickest method for finding the inverse z transform. The inversion integral of the z transform X(z) is given by Z-1 [X(z)] = = where C is a circle with its center at the origin of the z plane such that all poles of inside it If X(z) Residue z =a contains a multiple pole a of order m, then the residue at a is given by, = [(z-a)m X(z) are

Example 2.4 Given, E(z) = Determine e(k) using each of the above three methods for inverse z transform. solution, i) Using power series method: By direct division, z-1 + 3 z-2 + 7 z-3 + 15 z-4 +. z2 3z +2 )z z 3 + 2z-1 3 - 2 z-1 3 9 z-1 + 6 z-2 7 z-1 6 z-2

7 z-1 21 z-2 + 14 z-3 -15 z-2 - 14 z-3 +.. Thus, E(z) = z-1 + 3 z-2 + 7 z-3 + 15 z-4 +. , By compairing this infinite series expansion of E(z) with E(z) = we obtain, e(o) =0, e(1) = 1, e(2) = 3, e(3) = 7 and so on.

ii) using partial fraction expansion E(z) = = 2 The partial fraction expansion of i.e. E(z) = = hence, e(k) = [ - (1)k + 2k] u(k). is found to be Recall Z { ak u(k)} =

iii) using residue theorem method E(z) = e(k) = = + Residue z =1 = z =1 = [2k - 1] u(k) + z=2 z=2 =

= Residue

Example 2.5 Given, E(z) = Determine e(k) using residue theorem method for inverse z transform. solution e(k) =

= Residue z =1

+ Residue z=2

Notice the repeating poles at z=1. We have for repeating poles, Residue z =a Residue z =1 = * + z=1 = z=1 =k similarly, Residue = = 2k-1 = * + = [(z-a)m X(z)

z =2 Hence, e(k) = [ K + 2k-1 ] u(k).

MATLAB approach In Matlab, inverse z transform of G(z) can be obtained by finding the response of the system to the Kronecker delta input. The following program shows us how. Consider G(z) =
% Determining inverse z-tranform of G(z) using Matlab % Define numerator and denominator of G(z) num =[0 1 0] den =[1 -3 2] %Kronecker delta input x and filter command x = [1 zeros(1,30)]; y=filter(num, den,x) % Next, to plot the response v= [0 30 -1 1] axis(v); k=0:30; plot(k,y, 'o') grid title('system response to kronecker delta input') xlabel('k') ylabel('y(k)')

Upon execution of the program the following output response and the plot for y(k) is obtained for the value of k ranging from 0 to 30 y =1.0e+009 * Columns 1 through 10 0 0.0000 0.0000 0.0000 0.0000 0.0000 0.0000 0.0000 0.0000 0.0000

Columns 11 through 20 0.0000 0.0000 0.0000 0.0000 0.0000 0.0000 0.0001 0.0001 0.0003 0.0005

Columns 21 through 30 0.0010 0.0021 0.0042 0.0084 0.0168 0.0336 0.0671 0.1342 0.2684 0.5369

Column 31 1.0737

12

x 10

system response to kronecker delta input

10

y(k)

10

15 k

20

25

30

2.6 Z TRANSFORMATION METHOD FOR SOLVING DIFFERENCE EQUATION Example 2.6 Solve the following difference equation by the use of z transform method: m(k) 0.75 m(k-1) +0.125m(k-2) = e(k) + e(k-1), e(k) = 0.6k u(k) solution i) z transformation of delays/ advances: Z {m(k-1)} = z-1 [M(z) + = z-1 M(z) + m(-1) Z {m(k-2)} = z-2 [M(z) + = z-2 M(z) +z-1 m(-1) + m(-2) Z {e(k-1)} = z-1 [E(z) + = z E(z) + e(-1)
-1

m(-1) = m(-2) =1,

ii) Z transformation of the difference equation M(z) 0.75 [z-1 M(z) + m(-1)] + 0.125 [z-2 M(z) +z-1 m(-1) + m(-2)] = E(z) + z-1 E(z) + e(-1)

or, we have,

M(z) [1- 0.75z-1 + 0.125 z-2] 0.625 + 0.25z-1 = E(z) [1 + z-1]

e(k) = 0.6k u(k) E(z) = then, M(z) [z2 0.75z + 0.125] = M(z) = + z(z + 1) + z(0.625z 0.125)

iii) Inverse z transform of the final response m(k) = Z -1 * = Z -1 * + + Z -1 * + +

using residue theorem method, Z -1 * += = + z=0.6 = 27.4 (0.6)k - 30 (0.5)k + 3.57 (0.25)k Similarly, Z -1 * += = + z=0.25 = [-0.125 (0.25)k + 0.75 (0.5)k ] u(k) m(k) = [ 27.4 (0.6)k - 29.25 (0.5)k + 3.445 (0.25)k ] u(k) z=0.5 + z=0.5 z=0.25

Try: m(k) + m(k -1) + m (k-2) = e(k) + e(k-1) m(-1) =1, m(-2) = 2 ; e(k) = (0.6)k u(k)
Ans: 0.935 (0.6)k - 3.86 (-0.5)k + 2.76 ( )k

Example 2.7 PI Controller Consider a PI controller with differential equation: m(t) = 2e(t) + Find: i) its difference equation using the best approach for integral approximation ii) Zero-state controller response if e(t) = u(t) iii) Complete response of e(t) = u(t), m(-1) = 0.5 solution, i) m(t) = 2e(t) + =

Using trapezoidal rule for integral approximation. i.e. Applying z transformation to the differential equation, =2+ * =2+ =

+ +

or, M(z) M(z) z-1 = 2.1 E(z) 1.9 E(z) z-1 or m(k) m (k-1) = 2.1 e(k) 1.9 e(k-1) which is the require difference equation

ii) Now for the zero state controller response, we have e(t) = u(t) E(z) = = M(z) = = m(t) = =

[2.1z 1.9] zk z =1

= 2.1 (k +1) 1.9k = [0.2 k + 2.1 ] u(k)

iii) Complete response we have, E(z) =

Z {e(k-1)} = z-1 [E(z) + = z E(z) + e(-1) = z-1 E(z) Z {m(k-1)} = z-1 [M(z) + = z-1 M(z) + m(-1) = z-1 M(z) + 0.5
-1

[ since, e(-1) = 0] ]

[ since, e(-1) = 0]

Now, Applying z transformation to the differential equation, m(k) m (k-1) = 2.1 e(k) 1.9 e(k-1) M(z) - z-1 M(z) + 0.5 = 2.1 E(z) -1.9 z-1 E(z) or, or, M(z) [1 z-1] = [2.1 1.9 z-1] E(z) 0.5 M(z) [1 z-1] = [2.1 1.9 z-1 ]

0.5

or M(z) =

m(t) = =

0 z=1

= 1.6 (k +1) - 0.9k 0.5 (k -1) = [0.2k + 2.1 ] u(k)

Try: A PID controller with input e(t) and output m(t) is described according to m(t) = 0.5 e(t) + 2 i) Determine the difference equation for this controller using the backward differential and trapezoidal methods of approximating derivatives and integrals respectively. ii) Determine the zero-state unit step response of the controller.

MATLAB Approach Condisder the discrete-time control system defined by the transfer function = The following Matlab program gives us the response to a unit-step function. The resulting plot is given below with k ranging from 0 to 40.
% Unit step response % Define numerator and denominator of G(z) num =[0 0.467 -0.339]; den=[1 -1.533 0.661]; r=ones(1,41); v=[0 40 0 1.6]; axis(v); k=0:40; y=filter(num,den,r); plot(k,y, 'o') grid title('Unit step response') xlabel('k') ylabel('y(k)')

Unit step response 1.4

1.2

0.8

y(k)
0.6 0.4 0.2 0 0

10

15

20 k

25

30

35

40

2.7 STATE VARIABLE ANALYSIS State variable model of a discrete-time system consists of a set of first-order difference equations relating state variables x1(k), x2 (k),..xn(k) of the discrete-time system to the input u(k) and also the output y(k) to the state variables and the input. Besides, difference equations and transfer function, there exists a third way of representing a lineartime-variant discrete-time system, namely graphical method. There are two different ways of representing a discrete-time system in graphical method: i) Simulation Diagram The following key points need to be kept in mind while drawing a simulation diagram Simulation Diagram uses difference equation. There will be no change is sign from the difference equation while drawing simulation diagram

ii) Signal Flow Graph The following key points to kept in mind while drawing a signal flow graph Signal from graph uses transfer function There will be change in the sign of denominator of the transfer function, in the signal flow graph Numerator of the transfer function is drawn as the forward loop where as the denominator is drawn as the backward loop.

Example 2.8 Given a difference equation: m(k) + m(k-1) + m(k-2) = e(k) + 2 e(k-1) + 3 e(k-2) Obtain: i) its transfer function ii) the signal flow graph and a corresponding state matrix equation for a control canonical form.

solution Applying z transformation, M(z) + or, z-1 M(z) + z-2 M(z) = E(z) + 2 z-1 E(z) + 3 z-2 E(z) =

Now, that we have the transfer function the signal flow graph can drawn as below:

1 2

x2(k +1)
U(z) E(z) z-1

x1(k +1) x2(k)


z-1

x1(k)

M(z)

-5/6

-1/6

From the signal flow graph, the state matrix equations for the control canonical form can be written as: x1 (k + 1) = x2 (k) x2 (k + 1) = u(k) x2 (k) - x1 (k)

m(k) = 3 x1 (k) + 2 x2 (k) + x2 (k +1) = 3 x1 (k) + 2 x2 (k) + u(k) = x1 (k) + x2 (k) + u(k) x2 (k) - x1 (k)

]=[ +[

][

0 ] + * + u(k)

m(k) = *

] + [1] u(k)

Example 2.9 Draw a signal flow graph and obtain the state matrix equation for the following block diagram
e(k)

e(k - 1)

e(k - 2)

e(k - 3)

-3

-1

m(k)

m(k - 1)

+
-1

solution, Firstly we need to obtain the difference equation from the given block diagram which is determined as: m(k) m(k-1) = -e(k) 3 e(k-1) + 2 e(k-2) e(k-3) Applying z transformation to the difference equation, M(z) - z-1 M(z) = - E(z) - 3 z-1 E(z) + 2 z-2 E(z) - z-3 E(z) = Now, that we have the transfer function the signal flow graph can drawn as below:
-1

x3(k +1)
U(z) E(z) z-1

x2(k +1) x3(k)


z-1

x1(k +1) x2(k)


z-1

x1(k)

-1

M(z)

the state matrix equations for the control canonical form can be written as: x1 (k + 1) = x2 (k) x2 (k + 1) = x3 (k) x3 (k + 1) = e(k) + x3(k)

m(k) = - x3 (k + 1) - 3 x2 (k + 1) + 2 x2 (k ) x1 (k) = -x1 (k) + 2 x2 (k) - 4 x3 (k) e(k) Hence, the state matrix equation in CCF is given by, [ 2 0 ] = [0 0 2 0 0 0 ][ 2 0 ] + [ 0 ] e(k)

m(k) =

[ 2

] + [1] e(k)

Example 2.10 Given a difference equation: m(k) + m(k-1) + m(k-2) = e(k) + 2 e(k-1) + 3 e(k-2)

Obtain its state matrix equation in observer canonical form. solution As obtained in example 2.8, the transfer function of the above differential equation is given by =

e(k) = u(k)

x1(k + 1) x2(k +1)


-1/6

x1(k)
m(k)

x2(k)
-5/6

m(k) = x1 (k) + u(k) x1 (k + 1) = x2 (k) + 2 u(k) = x2 (k) + 2 u(k) =m(k) [x1 (k) + u(k)]

x1 (k) + x2 (k) + u(k)

x2 (k + 1) = 3u(k) - m(k) = 3u(k) - x1 (k) - u(k) = - x1 (k) + u(k)

Hence, the state matrix equation in OCF is given by, [ ]=[ 0 [ ][ ] + [ ] u(k)

0 2

m(k) =

] + [1] u(k)

Example 2.11 Given a transfer function, G(z) = Obtain: i) Simulation Diagram ii)corresponding CCF and OCF solution or, = 2 + = E(z) [ 2 =

or, M(z) *

or m(k) + 2 m(k-1) + m (k-2) +

m(k-3) = e(k-1) + 2e(k-2) +e(k-3)

i) From the difference equation the simulation diagram can be drawn as:
e(k) = u(k)

-1

-1

-1

1 m(k) m(k -1 ) m(k -2 )

-1

-1

-1

ii) Controllable canonical form: In order to obtain the CCF, we first draw the signal flow graph from the transfer function =

1 U(z) E(z)

x3(k +1)
z-1

x2(k +1) x3(k)


z-1

x1(k +1) x2(k)


z-1

x1(k)

M(z)

-2

-1

-1/2

Hence, the state matrix equation in the CCF is given by: x1 (k + 1) = x2 (k) x2 (k + 1) = x3 (k) x3 (k + 1) = u(k) -2 x3(k) x2 (k) - x1 (k) m(k) = x1 (k) + 2 x2 (k) + x3 (k)

Hence, the state matrix equation in CCF is given by, [ 2 0 ]=[ 0 0 0 2 ] ][ 2 0 ] + [ 0 ] e(k)

m(k) =

[ 2

iii) Observer canonical form


e(k) = u(k)

x3(k +1)
-1/2

x3(k)

x2(k)

x1(k)

m (k)

-1

x2(k +1)
-1

-1

x1(k +1)
-2

-1

Hence, the state matrix equation in the OCF is given by: x1 (k + 1) = x2 (k) + e(k) - 2 x1 (k) x2 (k + 1) = x3 (k) + 2e(k) - x1 (k) x3 (k + 1) = e(k) - x1 (k) m(k) = x1 (k)

Hence, the state matrix equation in CCF is given by, 2 [ 2 ]=[ 0 0 0 0 ][ 2 ] + [ 2 ] e(k)

m(k) =

0 [ 2

Try Given the difference equation: y (k +2) + 6 y(k +1) + 5 y(k) = 3 e(k +2) + e (k+1) + 2 e(k) Obtain the state variable matrix equation for i) CCF ii) OCF

2.9 OTHER STATE VARIABLE FORMULATIONS i) Parallel form of state variable In parallel form of state variable, the transfer function is expanded by partial fraction such that each delay unit can be drawn parallel to each other in the diagram.
z-1

E(z) z-1

M(z)

i) Cascade form of state variable In cascade form of state variable, the transfer function is arranged in such a way that each delay unit is cascaded to the other in the diagram.
z-1 E(z) z-1 M(z)

Example 2.12 Given, m(k) + m(k-1) + m(k-2) = e(k) Obtain its: i) Parallel form of state variable ii) Cascade form of state variable

Solution M(z) + or, z-1 M(z) + z-2 M(z) = E(z) = = = By partial fraction expansion, = =
x1(k + 1)
1 z-1

x1(k)
1.47

E(z) 1

0.5

M(z)

x2(k + 1)

z-1

x2(k)

0.64

0.33

From the above diagram, the state matrix equation can be formulated as: x1 (k + 1) = e(k) + 0.5 x1 (k) x2 (k + 1) = 0.33 x2 (k) + e(k) m(k) = x1 (k) then, [ 2 ]=* 0 0 0 [ 0 2 0 +[ ] 2 ] + * + e(k)

m(k) =

Next, for the cascade form of the state variable the transfer function can be written as, = = = . .

E(z)

z-1

x2(k)

x1(k + 1)

z -1

M(z)

x2(k + 1)

x1(k)

0.5

0.33

From the above diagram, the state matrix equation can be formulated as: x1 (k + 1) = x2 (k) + 0.33 x1 (k) x2 (k + 1) = 0.5 x2 (k) + e(k) m(k) = x1 (k) then, [ 2 ]=* 0 [ 0 0 2 ] 0 +[ 2 0 ] + * + e(k)

m(k) =

Try Given the difference equation: y (k +2) + 6 y(k +1) + 5 y(k) = 3 e(k +2) + e (k+1) + 2 e(k) Obtain the state variable matrix equation for i) Parallel form ii) Cascade form

Das könnte Ihnen auch gefallen